DAMPAK PENERIMAAN RETRIBUSI DAERAH, PAJAK DAERAH, DAN PENDAPATAN SAH LAINNYA ATAS PENDAPATAN ASLI DAERAH (STUDI PADA KABUPATEN/KOTA PROVINSI JAWA TIMUR TAHUN 2014-2018). - Afifah, Riska Ardina Nur; Nurdiwaty, Diah (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to determine the effect partially and simultaneously local taxes, regional levies and other legal income on local revenue (PAD). The variables in this study are the dependent and independent variables, where the dependent variable is Local Own Revenue and the independence of Regional Taxes, Retribution and Other Legal Income. This research uses quantitative methods. The population in this study were 38 cities / regencies in East Java for the period 2014-2018 and there were 190 samples to be studied. The data used is secondary data obtained from the website of the Directorate General of Fiscal Balance and the Central Bureau of Statistics with the website address (www.djpk.kemenkeu.go.id) and (www.bpsjatim.go.id). The analysis technique used is Panel Data Regression with STATA 14. The results of this study are that local taxes have a significant impact on local revenue in the City / Regency of East Java; Retribution has a significant impact on local revenue in the city / regency of East Java; and other legal revenues have a significant impact on local revenue in the city / regency of East Java.